EFFECT OF QUALITY IN MATERNAL AND CHILD HEALTH (MCH) SERVICE ON THE SATISFACTION OF MOTHER IN PUSKESMAS KENYAMNDUGA DISTRICT - Rakhel Gwijangge , Indar , Muhammad Alwy Arifin , Sukri , Hasnawati Amqam, A. Ummu Salmah (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The government is still seriously concerned about maternal and child health at this time. The high mortality rate for mothers, babies and children under five makes MCH a top priority in the Ministry of Health’s program. This study aims to analyze the effect of the quality of MCH services on patient satisfaction at Puskesmas Kenyam, Nduga Regency. This type of research is a quantitative study using an observational survey approach. . The design of this study used a cross sectional approach. Sampling used total sampling so that the sample in this study was 72 respondents. The results showed that there was a significant relationship between responsiveness, assurance, direct evidence of empathy, and reliability with respondent satisfaction (p = 0.000). at the Kenyam Puskesmas in Nduga Regency in 2020.This study concludes that Jaminan and Direct evidence is a variable that has a significant and joint effect on maternal satisfaction at Puskesmas Kenyam, Nduga district in 2020. While responsiveness, empathy, reliability have a significant effect but do not jointly affect maternal satisfaction at Puskesmas Kenyam, Nduga district. the year 2020.Based on the research conclusions, it is suggested to the MCH service officers at the Kenyam Puskesmas, Nduga district, to improve their responsiveness, show empathy in the form of genuine and friendly caring, professionalism as direct evidence in providing services, and to stakeholders at the Kenyam Puskesmas, Nduga district. further enhancing the reliability capability of improving existing facilities and infrastructure, especially in MCH services, as a guarantee for the creation of satisfaction for MCH service users.